Hidróxido de cálcio (Ca(OH)2) e bactérias heterofermentativas como aditivos em silagens de cana-de-açúcar (Saccharum officinarum L.) para alimentação de ruminantes - Mohallem, Renata de Freitas Ferreira (2009)
The objective of this study was to evaluate the effects of biological and chemical additives on the fermentative characteristics and nutritional quality of sugarcane (IAC 862480) silages. The trial was carried out in a completely randomized experimental design with factorial scheme of six treatments and three replicates per treatment. The treatments were based on the sugarcane silage additive: heterolactic bacteria (Lactobacillus buchneri), bacteria + enzyme (Propionibacterium sp associated with amylolytic enzymes), 0,8% Ca(OH)2, 1,3% Ca(OH)2, 1,8% Ca(OH)2 and crude sugarcane silage (control treatment). The treatments with Propionibacterium sp and amylolytic enzymes and with L. buchneri had bromatological results similar to the control treatment. The Propionibacterium sp and amylolytic enzymes silages showed lower ethanol levels when compared to the crude sugarcane silage. However, this fact does not indicate the superiority of Propionibacterium sp additive compared to control, since the dry matter recovery and the dry matter in vitro digestibility did not differed statically(P> 0,05) from the control treatment. Silages inoculated with L. buchneri reduced the level of ethanol and showed good dry matter recovery, but did not surpass the results presented by treatments with hydrated lime. Silages with alkaline additives (calcium hydroxide) were more effective in reducing the sugarcane s cell wall compounds than the control treatment, improving the dry matter in vitro digestibility. Treatments with calcium hydroxide were effective in controlling the alcoholic fermentation and had lower loss of dry matter.